The Existence, Transcendence, and Evolution of the Subject—A Method Based on Subject Information - Zheng Wu (Computer Sciences & Mathematics Forum)
Based on the modern dilemma of the existence of the subject, information philosophy is transformed into ontological “subject information”, and the basic elements of the virtual dimension and the real dimension are abstracted from it. And then, with the help of the alternate transformation of the virtual dimension information and the real dimension information, the existence and evolution of subject information are explored.